Focusing on some special problems of vocabulary: english-spanish - Valdivieso V., Grace; Salgado C., Noelia
This thesis is intended as a manual of instruction and guidance principally for English-speaking students of Spanish, and secondarily to help Spanish-speakers who are studying English. The first part focuses on "false cognates," that is, words which are cognates but which, for some reason, have come to have widely different meanings in the two languages. Perhaps the best example of this kind of word is the "embarrassed" one: in English this word means simply "ashamed," but in Spanish it means "pregnant." It is easy to imagine how this discrepancy could give rise to embarrassing (in the English sense) situations - especially if used by an English-speaking male who doesn´t know about the Spanish sense of the word. And there is a whole class of words like this. The second part deals with "missing cognates," that is, words that exist in one of the two languages and that one would expect to exist in a similar form in the other language, but which, for some reason, do not. Again, there is a whole set of words like this. The last part is a catalog of Spanish words that are derived from Arabic, which, of course, represent an area of particular difficulty for the English-speaking student, since there is no chance of deducing meaning, at least partially, since there are very few cognates that exist between English and Arabic. The aim of this section is to give the English-speaking learner of Spanish an aid in his learning